Synthesis of Some Coumarinyl Chalcones of Pharmacological Interest - Jayashree, B.S.; Yusuf, Shakkeela; Vijay Kumar, D. (Asian Journal of Chemistry, 2010)
Coumarins are group of secondary plant metabolites found to exhibit important pharmacological activities. Some of their 3-substituted derivatives such as novobiocin, coumaromycin and chartencin are known to exhibit antibacterial activity. The reports on chalcones address their useful biological activity. In the present study, three acetylcoumarins were condensed with different aromatic aldehydes to obtain coumarinyl chalcones. 3-Acetylcoumarins were synthesized by Pachmann reaction and were condensed with different substituted aromatic aldehyde to obtain coumarinyl chalcones (1-12). The synthesized test compounds were characterized by their TLC, melting point, IR, 1H NMR and Mass spectral studies and evaluated for various pharmacological activities such as, antioxidant, antiinflammatory, analgesic and antibacterial activity. Out of the randomly selected test compounds, none of them exhibited antioxidant activity. However, compounds 7 and 9 exhibited fairly good analgesic activity compared to that of standard diclofenac sodium. Further, three compounds were randomly selected for antiinflammatory activity and found to be moderately active. Finally, all the test compounds were screened for their antibacterial activity, out of which, few were found to be moderately active against gram positive organisms while compound 10; a bromo substituted derivative of coumarin has shown zone of inhibition at 18 when compared with that of the standard streptomycin showing inhibition at 10 against K. pneumonia. It was found that halogen substitution at 6th position on coumarinyl chalcones has greater influence on analgesic activity than unsubstituted ones, while for antiinflammatory activity unsubstituted ones are more appropriate. Further, compound 10 was found to be active against K. pneumonia.